Actividad catalítica de complejos p-R-cinamato de Ce(III), Nd(III) y Sm (III) en la oxidación de β-pineno y canfeno (2017)
The synthesis of nine lanthanide complexes of cerium, neodymium and samarium with ligands trans-cinnamate (L1), trans-p-chlorocinnamate (L2) and trans-p-methoxycinnamate (L3) was carried out. The characterization performed by FT-IR spectroscopy, thermal analysis (TGA and DSC) and elemental analysis. The compounds obtained were used as catalysts for the oxidation of camphene and β-pinene, using hydrogen peroxide (30%) and peracetic acid (12%) as oxidizing agents. In the oxidation of camphene, the [Nd(L2)3] complex, showed the highest conversion (97.99%) with a selectivity of 84.05% towards 3-can phenyl carboxylic acid, while in β-pinene oxidation, the [Ce(L3)3.2H2O] complex, showed the highest conversion (82.62%) with a selectivity towards the nopinone of 70.52%.